2022
DOI: 10.3390/ma15051798
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study on Friction and Wear Performance of Hot Extrusion Die Materials

Abstract: For the aluminium alloys produced by the hot extrusion process, the profile is shaped according to the bearing at the exit of the extrusion die. The tribological process has significant effects on the die service life, profile dimensional tolerances, and profile surface finish. Recently, new technologies have been introduced to the hot extrusion die, such as cemented carbide insert die and surface coating. However, under hot extrusion working conditions, quantitative studies on their friction and wear performa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Hot-working die steels are widely used in the hot-working dies of parts prepared by hot forging and hot extrusion [1,2]. Their service temperature during hot forging and hot extrusion can exceed 500 °C-600 °C (local temperature can reach almost 700 °C) [3,4]. Furthermore, the dies suffer dry wear and heating impact when directly contacting hot metals in an unlubricated environment.…”
Section: Introductionmentioning
confidence: 99%
“…Hot-working die steels are widely used in the hot-working dies of parts prepared by hot forging and hot extrusion [1,2]. Their service temperature during hot forging and hot extrusion can exceed 500 °C-600 °C (local temperature can reach almost 700 °C) [3,4]. Furthermore, the dies suffer dry wear and heating impact when directly contacting hot metals in an unlubricated environment.…”
Section: Introductionmentioning
confidence: 99%
“…Authors of work [ 19 ] concluded that many defects in the extruded products occur because of the conditions of the dies and tooling. The mechanisms of die surface wear were investigated in the work of Zhao et al [ 20 ].…”
Section: Introductionmentioning
confidence: 99%